"Can you send an ambulance please?": a comparison of callers' requests for emergency medical dispatch in non-stroke and stroke calls. Issue Volume 31:Issue e1(2014) (13th July 2013) - Leathley, Michael J; Jones, Stephanie P; Gibson, Josephine M E; Ford, Gary A; McAdam, Joanna J; Quinn, Tom; Watkins, Caroline L
Abstract : Background: Identifying 'true stroke' from an emergency medical services (EMS) call is challenging, with over 50% of strokes being misclassified. In a previous study, we examined the relationship between callers' descriptions of stroke symptoms to the emergency medical dispatcher and the subsequent classification and prioritisation of EMS response. The aim of this subsequent study was to explore further the use of keywords by callers when making emergency calls, comparing stroke and non-stroke calls. Methods: All non-stroke calls to one EMS dispatch centre between 8 March 2010 and 14 March 2010 were analysed. These were compared with the stroke calls made to one EMS dispatch centre between 1 October 2006 and 30 September 2007. Content analysis was used to explore the problems described by the caller, and findings were compared between non-stroke and stroke calls. Results: 277 non-stroke calls were identified. Only eight (3%) callers mentioned stroke, 12 (4%) and 11 (4%) mentioned limb weakness and speech problems, respectively, while no caller mentioned more than one classic stroke symptom. This contrasted with 473 stroke calls, where 188 (40%) callers mentioned stroke, 70 (15%) limb weakness and 72 (15%) speech problems, and 14 (3%) mentioned more than one classic stroke symptom. Conclusions: People who contact the EMS about non-stroke conditions rarely say stroke, limb weakness, speech problems or facial weakness. These words are more frequently used when people contact the EMS about stroke, although many calls relating to stroke patients do not mention any of these keywords.